Striving for zero traditional and non-traditional healthcare-associated infections (HAI): a target, vision, or philosophy - Jaffar A. Al-Tawfiq (Antimicrobial Stewardship & Healthcare Epidemiology)
Healthcare-associated infections (HAIs) are a major global health concern, affecting millions of patients each year across a variety of healthcare settings. Originally known as nosocomial infections, HAIs now include infections acquired during medical care other than acute-care hospital admissions. These infections, which range from traditional (eg, CLABSI, CAUTI, SSI, VAP) to non-traditional (eg, outbreaks, EIDs, MDROs), pose a variety of challenges and have a significant impact on patient care outcomes. According to studies, patients with HAIs have longer hospital stays, higher mortality rates (ranging from 7% to 64.6%), and higher healthcare costs as a result of their extended care needs. This review will delve into the prevalence, consequences, and management strategies for both traditional and non-traditional HAIs.